Chirality-selected crystal growth and spin polarization over centimeters of transition metal disilicide crystals. (1st January 2023) - Kousaka, Yusuke; Sayo, Taisei; Iwasaki, Satoshi; Saki, Ryo; Shimada, Chiho; Shishido, Hiroaki; Togawa, Yoshihiko
Abstract: We performed a chirality-controlled crystal growth of transition metal disilicide NbSi2 and TaSi2 by using a laser-diode-heated floating zone (LDFZ) method. The crystal chirality was evaluated in the crystals of centimeters in length by performing single crystal X-ray diffraction as well as probing a spin polarization originating from the chirality-induced spin selectivity (CISS) effect. The crystals of right-handed NbSi2 and of left-handed TaSi2 were obtained in the conventional LDFZ crystal growth, while the left-handed NbSi2 and right-handed TaSi2 crystals were grown by the LDFZ method with the composition-gradient feed rods. The spin polarization via the CISS was observed over centimeters in the NbSi2 single crystals and the sign of the CISS signals was dependent on the chirality of crystals. The correlation between the crystal chirality and CISS signals indicates that the CISS measurements work as a non-destructive method for chirality determination even in centimeter-long specimens.